A modified analytical procedure for the determination of carbaryl, carbofuran and methomyl residues in agricultural soil and river water samples from La Trinidad, Benguet and Aurora, Isabela, Philippines - Cid, Abigail P.; del Mundo, Florian R.; Espino, Maria Pythias B. (2006)
A modified analytical procedure was developed for commonly used carbamate pesticides such as carbaryl, carbofuran and methomyl in agricultural soil and river water using high pressure liquid chromatography (HPLC) with UV detection and compared to US EPA 8318A, US EPA 531 and US EPA 3540 methods. Soil samples were soxhlet extracted with acetonitrile followed by a silica gel cleanup using 50:50 (v/v) acetonitrile-acetone. Carbaryl, carbofuran and methomyl in river water samples were extracted using graphitized carbon black followed by elution using methanol and 80:20 (v/v) dichloromethane-methanol. The recoveries of the pesticides from river water (n = 3) and agricultural soil (n = 4) ranged from 88.69 ± 10.21% to 120.50 ± 11.84% with method detection limits of 2.30 ± 0.20 µg L-1 to 3.90 ± 0.36 µg L-1 for river water (n = 6) and 0.04 t 0.01 µg g-1 to 0.27 0.01 µg g-1 for agricultural soil (n= 6 to 8). The modified procedure was applied to the determination of levels and persistence of carbaryl, carbofuran and methomyl in agricultural soil samples taken from cultivated lands in La Trinidad, Benguet and Aurora, Isabela, and water samples from bodies of water within the study areas. Carbaryl was found to be more persistent in agricultural soil with a history of pesticide applications while methomyl tends to persist in river water.
Keywords: Agricultural chemicals